2014
DOI: 10.1007/s00418-014-1234-x
|View full text |Cite
|
Sign up to set email alerts
|

Human osteoarthritic knee cartilage: fingerprinting of adhesion/growth-regulatory galectins in vitro and in situ indicates differential upregulation in severe degeneration

Abstract: The apparent connection of galectin-3 to chondrocyte survival and osteoarthritis-like cartilage modifications in animal models provided incentive for the mapping of seven members of this family of adhesion/growth-regulatory proteins in human cartilage specimens. Starting with work in vitro, RT-qPCR analyses and immunocytochemistry revealed gene transcription and protein presence in cultured OA chondrocytes, especially for galectin-1, galectin-3 and galectin-8. Immunohistochemistry in clinical specimens with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 50 publications
3
70
0
1
Order By: Relevance
“…In previous studies, we had revealed that several members of the galectin family are expressed in vivo in osteoarthritis (10), and that specific features of the chondrocyte glycophenotype are altered during osteoarthritic conditions (8,9). In this study, we focused on Galectin-1, by immunohistochemical analysis and work with human osteoarthritic chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, we had revealed that several members of the galectin family are expressed in vivo in osteoarthritis (10), and that specific features of the chondrocyte glycophenotype are altered during osteoarthritic conditions (8,9). In this study, we focused on Galectin-1, by immunohistochemical analysis and work with human osteoarthritic chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin sections of mildly and severely degenerated cartilage were stained with Safranin O (Sigma-Aldrich) (10). Thereafter, a varying number of regions (2-10 per patient, depending on availability of regions differing in degeneration) was graded according to the Mankin score (MS), as previously described (10).…”
Section: Histological Assessmentmentioning
confidence: 99%
See 3 more Smart Citations